2022
DOI: 10.1093/bioinformatics/btac493
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cellular cancer mechanisms through pathway-driven data integration

Abstract: Motivation Cancer is a genetic disease in which accumulated mutations of driver genes induce a functional reorganisation of the cell by reprogramming cellular pathways. Current approaches identify cancer pathways as those most internally perturbed by gene expression changes. However, driver genes characteristically perform hub roles between pathways. Therefore, we hypothesise that cancer pathways should be identified by changes in their pathway-pathway relationships. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Through clustering enrichment analysis, we showed that graphlet adjacencies capture complementary biological functions in molecular networks. We also showed that A G 1 , A G 3 and A G 6 best capture cancer disease mechanisms, outperforming standard adjacency (Windels et al, 2022).…”
Section: Graphlet Adjacencymentioning
confidence: 83%
“…Through clustering enrichment analysis, we showed that graphlet adjacencies capture complementary biological functions in molecular networks. We also showed that A G 1 , A G 3 and A G 6 best capture cancer disease mechanisms, outperforming standard adjacency (Windels et al, 2022).…”
Section: Graphlet Adjacencymentioning
confidence: 83%
“…Recent approaches for deciphering these complex data are based on network embedding techniques [2,3]. These algorithms aim to find the vectorial representations of the network nodes in a low-dimensional embedding space spanned by a system of coordinates (a.k.a., embedding axes) while preserving the structural information of the network [2,4]. Defining an optimal number of dimensions of the embedding space is key to properly capturing the structural information of the network.…”
Section: Introductionmentioning
confidence: 99%